ESG and AI competences in Polish enterprises during the twin transition - Zwolińska, Danuta (Ekonomia i Prawo. Economics and Law, 2026)
Motivation: The dynamically changing needs of the labour market lead to the emergence of new approaches to career development and management. This is due to rapid technological changes and adaptation requirements imposed by the European Union (in particular the Corporate Sustainability Reporting Directive (CSRD) of 16 December 2022). The niche nature of ESG (E – Environment, S – Social Responsibility and G – Corporate Governance) specialisations has created a demand for specialists who are currently lacking in the market. In addition, technological changes and developments in artificial intelligence have accelerated. It is therefore worth determining which skills are currently most in demand. Aim: This article aims to examine what employee competences in modern technologies and in the area of ESG (E – Environment, S – Social Responsibility and G – Corporate Governance) are needed and critical for companies. Results: The analysis was conducted on data from a pilot survey based on the author's own questionnaire. The sample was selected using the quota sampling method, taking into account the dominant type of activity according to the Polish Classification of Activities (PKD). The survey was developed based on guidelines from the EU, including the European Sustainability Competence Framework (GreenComp), the European Digital Competence Framework (DigComp), as well as the Global Skills and Competency Framework for a Digital World. This facilitated the identification of key competences needed in today's turbulent environment. These competences become the basis for choosing a path for upgrading or changing the competences of employees. This is necessary in order to adapt to change and remain competitive on the market. Further research should focus on young adults entering the labour market in order to improve their digital and green skills.